2018
DOI: 10.1016/j.memsci.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

An advanced online monitoring approach to study the scaling behavior in direct contact membrane distillation

Abstract: One of the major challenges in membrane distillation (MD) desalination is scaling, mainly CaSO 4 and CaCO 3. In this study, in order to achieve a better understanding and establish a strategy for controlling scaling, a detailed investigation on the MD scaling was performed by using various analytical methods, especially an in-situ monitoring technique using an optical higher VCF values. In addition, CaCO 3 alone in feed solution did not affect the scaling, however, when CaSO 4 was added to CaCO 3 , the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 31 publications
(37 reference statements)
1
29
0
Order By: Relevance
“…fouling behavior in MD, a real-time monitoring is necessary (Lee et al, 2018). Particularly for MD that is a thermal separation process and where the fouling structure is not maintained when operation is shut-downed and samples are taken from the membrane module.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…fouling behavior in MD, a real-time monitoring is necessary (Lee et al, 2018). Particularly for MD that is a thermal separation process and where the fouling structure is not maintained when operation is shut-downed and samples are taken from the membrane module.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In agreement with other studies [ 69 , 70 ], the scaling observed on the membrane surface of no spacer ( Figure 5 b) and standard spacer ( Figure 5 c) cases were attributed to the barite crystals deposition, which is subsequently confirmed by EDX analysis ( Figure 5 ). The composition of SGPW led to the formation of barium sulfate (BaSO 4 ), which has low solubility in water resulting in its scaling on membrane surface [ 71 ]. In the case of hole-type spacer, SEM image ( Figure 5 d) revealed smaller particles spreading over the membrane area.…”
Section: Resultsmentioning
confidence: 99%
“…Thought the in-situ analysis was possible to evaluate the formation of carbonate and sulfate crystals over time (Figure 9). The use of OCT was then proposed as a tool to monitor the scaling in thermal process that employs membrane [53]. Recently, Bauer et al [54] used the OCT to quantify the area covered by the scaling and the flux decline in a membrane distillation process.…”
Section: Monitoring Inorganic Foulingmentioning
confidence: 99%